Timber-framing construction in Herculaneum archaeological site: characterisation and main reasons for its diffusion - Stellacci, S.; Rato, V. (International Journal of Architectural Heritage, 2021)
Timber-framing is the most common mixed construction technique utilised by Romans and many other builders throughout history. However, archaeological evidence is scarce due to the overlapping urban land use and the perishability of the wooden skeleton. This paper focuses on timber frame wall — opus craticium — from Herculaneum, examined through a literature review and on-site analysis. The aim of this research is shedding light on the reasons for the diffusion of opus craticium through a critical analysis of Vesuvian archaeological evidence, among which the best-known is Casa a Graticcio (Insula III, 13–15, Herculaneum). The dichotomy between the written transmission of this technique and the construction practice in the Augustan epoch is also discussed. It is shown how the pervasiveness of this technique in Herculaneum arises from multiple reasons: firstly, the strong demand of new constructions and the need of heavy repairs during the Augustan Principate. Additionally, the anaerobic conditions resulting from the specific on-site burial in 79 AD allowed the conservation of the timber-framing.